1997
DOI: 10.1104/pp.115.2.463
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression in Ripening Banana Fruit

Abstract: During banana (Musa acuminata L.) fruit ripening ethylene production triggers a developmental cascade that is accompanied by a massive conversion of starch to sugars, an associated burst of respiratory activity, and an increase in protein synthesis. Differential screening of cDNA libraries representing banana pulp at ripening stages 1 and 3 has led to the isolation of 11 nonredundant groups of differentially expressed mRNAs. ldentification of these transcripts by partia1 sequence analysis indicates that two of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
119
3
11

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(142 citation statements)
references
References 30 publications
(27 reference statements)
9
119
3
11
Order By: Relevance
“…Type 1 MTs Blindauer et al, 2001) are expressed much higher in roots than in shoots (Hudspeth et al, 1996), whereas Type 2 MTs are found mainly in leaves (Hsieh et al, 1995;Zhou & Goldsbrough, 1994). Type 3 MTs are expressed abundantly in the ripe fruits (Clendennen & May, 1997;Ledger & Gardner, 1994;Reid & Ross, 1997), and expression of Type 4 MTs, also known as the Ec type, was only found in developing seeds so far (Chyan et al, 2005;Lane et al, 1987). A vast number of stimuli have been demonstrated capable of inducing MT genes expression in plants, including natural senescence (Bhalerao et al, 2003), hormones like ABA (Reynolds & Crawford, 1996), ethylene (Coupe et al, 1995), wounding and virus infection (Choi et al, 1996), heat shock (Hsieh et al, 1995), sucrose starvation (Hsieh et al, 1996), UV-light (Foley & Singh, 1994), cold and salt stress (Reid & Ross, 1997), etc.…”
Section: Metallothionein: Metal-binding Protein and Morementioning
confidence: 99%
“…Type 1 MTs Blindauer et al, 2001) are expressed much higher in roots than in shoots (Hudspeth et al, 1996), whereas Type 2 MTs are found mainly in leaves (Hsieh et al, 1995;Zhou & Goldsbrough, 1994). Type 3 MTs are expressed abundantly in the ripe fruits (Clendennen & May, 1997;Ledger & Gardner, 1994;Reid & Ross, 1997), and expression of Type 4 MTs, also known as the Ec type, was only found in developing seeds so far (Chyan et al, 2005;Lane et al, 1987). A vast number of stimuli have been demonstrated capable of inducing MT genes expression in plants, including natural senescence (Bhalerao et al, 2003), hormones like ABA (Reynolds & Crawford, 1996), ethylene (Coupe et al, 1995), wounding and virus infection (Choi et al, 1996), heat shock (Hsieh et al, 1995), sucrose starvation (Hsieh et al, 1996), UV-light (Foley & Singh, 1994), cold and salt stress (Reid & Ross, 1997), etc.…”
Section: Metallothionein: Metal-binding Protein and Morementioning
confidence: 99%
“…Noticeably, many studies have reported that plant MTs acted as protectants against oxidative stresses imposed by a dverse environmental conditions (Akashi et al 2004;Mir et al 2004;Wong et al 2004;Xue et al 2009;Samardzic et al 2010). In addition, other studies have highlighted the importance of plant MTs in plant growth and development, such as seed development 15 and germination (Brkljacic et al 2004;Yuan et al 2008), tissue senescence (Bhalerao et al 2003;Guo, Bundithya & Goldsbrough 2003), fruit ripeness (Clendennen & May 1997) and root development (Yuan et al 2008). For example, the expression of most Arabidopsis MT genes was dramatically increased in senescing siliques and leaves (Guo et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the change in phenolic content in immature green fruit unable to respond to ethylene might be under the control of developmental cues while in mature green fruit both ethylene and developmental cues might be involved. Recent progress on the ripening process in banana strongly suggests that the ripening process of banana peel tissue clearly differs from that of the pulp (Domínguez and Vendrell, 1994;Clendennen and May, 1997;Inaba et al, 2007), thus suggesting tissuespecific regulation of the ripening process in this species. Independent of climactic season and fruit physiological stage at harvest, phenol content accumulates differentially in peel tissue compared to pulp tissue during ripening.…”
Section: Fig 3 Modification Of Enthalpy Limits For the Wp And Dpmentioning
confidence: 99%